Integration of ethnomathematics in culturally responsive STEM education to foster computational thinking - Lestari, Wahyu; Dafik , Dafik; Isyati, Andini Norma (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2025)
This study aims to describe the implementation of culturally responsive STEM learning integrated with an ethnomathematics approach to enhance students’ computational thinking skills. The research employed a descriptive qualitative method and was conducted at SMA Zainul Hasan Genggong, involving 30 tenth-grade students (class X-A) and one mathematics teacher. Data were collected through observation, interviews, documentation, and bibliometric analysis using VOSviewer. The findings indicate that incorporating local cultural elements such as Madurese batik motifs, bamboo weaving, and traditional culinary units created meaningful and contextual learning experiences. Students showed clear progress in key components of computational thinking, including breaking down cultural tasks into smaller mathematical components, identifying geometric and symmetrical patterns in cultural artefacts, and developing structured steps to address practical problems. Both teachers and students responded positively, highlighting increased engagement, motivation, and collaboration during group projects. The teacher reported that students became more active, creative, and critical, while students expressed that learning felt more relevant and enjoyable. Word Cloud visualisation revealed dominant keywords such as culture, mathematics, patterns, symmetry, problem-solving, and collaboration, reflecting the strong connection between cultural contexts and STEM education. Bibliometric analysis further confirmed the interrelation between STEM, computational thinking, and contextual learning. These findings suggest that culturally rooted STEM learning not only enhances conceptual mastery but also fosters systematic, reflective, and creative thinking, positioning it as an effective strategy for addressing the challenges of 21st-century education.